Access to Oncology Drugs in Brazil: Juggling Innovation and Sustainability in Developing Countries. Issue 1 (2017) - Ades, Felipe
Brazil is a developing country of continental proportions and faces challenges in organizing an effective, universal, and affordable public health system. In a context of limited resources, the budget allocation to health care must be consistent with the health priorities of each population. The Brazilian population is ageing and the number of new cancer cases is likely to steadily increase in the near future. To deal with the extra cancer burden, strategies to match this future health necessity must be proactively put in place. Keeping the balance between the incorporation of a new drug and the sustainability of the public health system is a complex matter. Decisions for incorporation must be assessed, taking into consideration the ability of the drug to improve the public health in relation to its monetary impact. This is a societal discussion, and multiple stakeholders are involved in this process - from health authorities to pharmaceutical companies, researchers, and civil society. This article discusses the issues of incorporating a drug into the public health system and the strategies to improve access to innovative medicines, from the regulatory to the drug development perspectives.